Divergent roles of circMPP6 and its parental gene MPP6 in non-small cell lung cancer - Gao, Weijuan; Pan, Feng; Qiu, Kangping; Ou, Canhui; Tian, Fang; Yu, Chengtao (Frontiers in Cell and Developmental Biology, 2026)
BackgroundCircular RNAs (circRNAs) regulate cancer biology, but their relationships with parental genes remain unclear. We characterized circMPP6, derived from MPP6, and its interplay with MPP6 in non-small cell lung cancer (NSCLC).MethodscircMPP6 was validated by RNase R resistance and Sanger sequencing in A549 cells. Expression of circMPP6 and MPP6 was measured in 10 paired NSCLC tumors and adjacent-tissues. RNA-seq after gain-of-function of circMPP6, MPP6, and SLC7A11 was followed by enrichment analyses and chromosome-level DEG mapping. Proliferation was assessed by CCK-8 and xenografts. Lactate and glutathione were quantified, SLC7A11 protein measured by Western blot, and prognosis analyzed in GEO/TCGA.ResultsMPP6 trended upward in tumors, while circMPP6 was unchanged. circMPP6 and MPP6 were positively correlated in adjacent-tissues but not in tumors. Overexpression of circMPP6 and MPP6 yielded 765 and 334 DEGs, respectively, with shared enrichment of hypoxia-related pathways. 67 genes were upregulated by circMPP6 but downregulated by MPP6, also linked to hypoxia signaling. circMPP6-regulated DEGs were enriched on chromosome 19, whereas MPP6-regulated DEGs clustered on chromosome 17. Functionally, circMPP6 did not alter proliferation, MPP6 enhanced it, and co-expression attenuated MPP6-driven growth in vitro and in vivo. circMPP6 reduced intracellular lactate and glutathione; MPP6 minimally affected lactate and increased glutathione. Consistently, circMPP6 downregulated SLC7A11, whereas MPP6 upregulated it. High-risk circMPP6-driven signatures and high MPP6 expression associated with poorer prognosis.ConclusioncircMPP6 and MPP6 exert distinct, partially opposing effects on NSCLC growth. In the context of MPP6 overexpression, circMPP6 counteracts tumor-promoting programs, highlighting functional divergence between circRNAs and their parental genes.